The impact of a training program on developing the communication skills of a sample of fifth grade teachers (Journal of Hama University, 2019)
The current research aims at identifying the impact of a training program on developing the communication skills of a sample of the fifth grade teachers. The researcher use the experimental method. The research is applied to a sample of teachers (40 teachers), divided into two groups, and the other is a program-controlled observer. They are selected in a deliberate manner. After applying the program to the sample and applying the communication skills scale, the following results are obtained:- There are no statistically significant differences between the mean scores of the experimental and control groups in the tribal application of the communication skill scale- There are  statistically significant differences between the average scores of the experimental group in tribal and remote applications of the communication skill scale.- There are statistically significant differences between the mean scores of the experimental and control groups in the post-application of the communication skill scale.In the light of the results, the researcher proposed training courses for basic education teachers to train them on how to employ communication skills and use them in different educational situations with students, in addition to integrating the communication skills in the basic education curricula and training them, communicate